Study of heavy metal resistance genes in Escherichia coli isolates from a marine ecosystem with a history of environmental pollution (arsenic, cadmium, copper, and mercury). - Ashley S Tseng; Marilyn C Roberts; Scott J Weissman; Peter M Rabinowitz (PLoS ONE, 2023)
We analyzed whole genome sequences of 308 Escherichia coli isolates from a marine ecosystem to determine the prevalence and relationships of heavy metal resistance genes (HMRGs) and antibiotic resistance genes (ARGs), as well as the presence of plasmid sequences. We screened all genomes for presence of 18 functional HMRGs conferring resistance to arsenic, cadmium, copper, or cadmium/mercury. In subset analyses, we examined geographic variations of HMRG carriage patterns in 224 isolates from water sources, and sought genetic linkages between HMRGs and ARGs in 25 genomes of isolates resistant to antibiotics. We found high carriage rates of HMRGs in all genomes, with 100% carrying at least one copy of 11 out of 18 HMRGs. A total of 173 (56%) of the isolates carried both HMRGs and plasmid sequences. In the 25 genomes of antibiotic-resistant isolates, 80% (n = 20) carried HMRGs, ARGs, and plasmid sequences, while 40% (n = 10) had linked HMRGs and ARGs on their assembled genomes. We found no evidence of geographic variation in HMRG frequency, nor any association between locational proximity to Superfund sites and co-carriage of HMRGs and ARGs. Our study findings indicate that HMRGs are common among E. coli in marine ecosystems, suggesting widespread heavy metal presence in water sources of a region with history of environmental pollution. Further research is needed to determine the role HMRGs play in driving antimicrobial resistance in human pathogens through genetic linkage and the value their detection in environmental bacterial genomes may offer as an indicator of environmental heavy metal pollution.